Mountain pasture management by goat farmers: case of the Kabylia region (Algeria) - Mouhous A.; Kadi S.A.; Djellal F.; Berchiche M. (Innovation for sustainability in sheep and goats, 2019)
The aim of this study is to characterize goat breeders’ pasture management strategies. 16 goat farms, located in a steep mountainous area in Tizi-Ouzou, were monitored for one year. Results show that goat breeding, with flocks ranging from 5 to 136 head, is regarded as the principal activity and under extensive conditions. Feeding is primarily based on the exploitation of pastures. On average, animals spend 6 hour/day on pasture. Pastures are made up of natural meadows, maquis and forests. The surface area of these pastures varies during the year according to the seasons, from 5 to 9 ha / breeder. It is in autumn and winter when the grazing period is reduced, and therefore the animals’ requierements are not sufficiently covered. For this purpose, hay, stubble and limbing are used during this part of the year. Limbing concerns plant species such as Algerian oak, cork oak, ash, broom and olive leaves. In addition, the distribution of supplements is based on the goat’s milk production strategy (low, medium and high production). Animals receive, throughout the year, a small amount of supplements, on average 135 g/head/day. These supplements may be green fodder, straw or concentrates. The latter is initially intended for cows, and contains wheat bran, corn or barley.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)